Pendampingan Penyusunan Laporan Keuangan di CV. Malakewi Mitra Abadi - Mutiara Oktaviani Putri; Ulviana Agustina; Hasna Lutfi Indriani; Ersha Wiriani Safitri; Siti Rodiah (Universitas Katolik Widya Karya Malang, 2023)
Malakewi Mitra Abadi is a construction implementation company in the form of Commanditare Vennotschap. CV.Malakewi MItra Abadi has its address at Eka Tunggal Street, Pekanbaru City. For now the partner company or CV. Malakewi Mitra Abadi has problems, namely the lack of accurate financial information and financial records that are still basic. Therefore, the service team will create an information system that can produce appropriate, relevant, accountable and accurate information for internal and external interests. The first is providing assistance in the management of financial transactions carried out by Partners. Therefore, several approaches can be used to overcome this problem, such as counseling, socialization, methoring and implementation in assisting the preparation of financial reports.The results of this servive show that the knowledge and expertise on CV. Malakewi Mitra Abadi regarding the preparation of financial reports using the Miscrosoft Excel program or manually has increased. Financial reports that include accounting data are readily available to partners.